Cerita Rakyat Sebagai Sarana Pendidikan Karakter dalam Membangun Generasi Literat - Lizawati, Lizawati (Universitas Hamzanwadi, 2018)
The objectives of the study were to describe the values contained in Tan Nunggal and Bujang Nadi Dare Nandong folklore in Sambas district of West Kalimantan. Folklore Tan Nunggal and Bujang Nadi Dare Nandong live and thrive in Sambas society. Through folklore acquisition of information based on oral culture can create literary generation. Sensitivity and critical power in the surrounding environment are preferred as a bridge to the literary generation, which is a generation that has critical thinking skills on all information to prevent emotional reactions. This culture is what most Indonesians do not seem to have. The research method used qualitative descriptive method with data analysis technique using interactive analysis technique that is with steps, that is data reduction, display data, and conclusion drawing / verification. The researchers used a hermeneutic approach. Examination of data validity using theory and source triangulation. The research finds the existence of religious values, social values, and moral values in the folklore Tan Nunggal and Bujang Nadi Dare Nandong.Keywords: folklore, character education, and literary generation